To solve the equation \( 14(8m + 12) - 7 = -2 \), follow these steps:
Question 1: Correct Order of Steps
Step 1: Distribute the \( 14 \) across \( (8m + 12) \)
Step 2: Combine like terms.
Step 3: Add \( 7 \) to both sides to isolate the term with \( m \).
Step 4: Solve for \( m \).
Now for Question 2, let's solve the equation \( 14(3m + 2) - 7 = -2 \):
-
Distribute the \( 14 \): \[ 42m + 28 - 7 = -2 \] Simplifying gives: \[ 42m + 21 = -2 \]
-
Subtract \( 21 \) from both sides: \[ 42m = -2 - 21 \] \[ 42m = -23 \]
-
Divide by \( 42 \): \[ m = \frac{-23}{42} \]
Since none of the responses provided match this solution, it seems there may have been a misunderstanding of the equation you wanted to solve. Please double-check the original equation you're asking about.
If you're looking for a specific value among the given responses (m = 5, m = 6, m=18, m is equal to 6, m=20), none are correct based on the calculation for \( 14(3m + 2) - 7 = -2 \). Could you clarify the equation?